Analysis of surgical treatment of cervical spondylotic amyotrophy - Yu, Zhong; Zhang, Haofuzi; Wang, Yanjun (Frontiers in Surgery, 2024)
Background: Cervical spondylotic amyotrophy (CSA) is a special type of cervical spondylosis based on cervical degeneration, which is mainly manifested by weakness and atrophy of upper limb muscles without obvious sensory impairment. Various diagnostic and treatment strategies used; however, discrepancies exist. We tried to discuss diagnosing and treating CSA. Methods: 15 patients with CSA were diagnosed in the Orthopedics Department of the First Affiliated Hospital of Zhengzhou University, aged 42-70 years old. The duration of preoperative symptoms of amyotrophy was 6 to 240 months. 12 patients received surgical treatment, and 3 patients received conservative treatment. The patients were divided into two groups according to the site of preoperative amyotrophy. The manual muscle test was used to evaluate the patients' muscle strength pre-and postoperatively. Results: During postoperative follow-up, the muscle strength of 12 patients improved to different degrees compared to before surgery. The improvement effect was excellent in 2 cases, good in 6, and moderate in 4. There was no decrease in postoperative muscle strength compared with that before surgery. The satisfaction rate of the effect was 66.7%. The two groups had no statistically significant difference in preoperative muscle strength. The postoperative muscle strength of the proximal group was significantly better than that of the distal group. Conclusion: The surgical effect of CSA of the proximal type is significantly better than that of the distal type. The recovery effect of amyotrophy after surgery for distal type CSA is poor; thus, surgical treatment should be carefully considered.